Assessing the relationship between monoallelic PRKN mutations and Parkinson's risk. Issue 1 (15th January 2021) - Lubbe, Steven J; Bustos, Bernabe I; Hu, Jing; Krainc, Dimitri; Joseph, Theresita; Hehir, Jason; Tan, Manuela; Zhang, Weijia; Escott-Price, Valentina; Williams, Nigel M; Blauwendraat, Cornelis; Singleton, Andrew B; et al.
Abstract: Biallelic Parkin ( PRKN ) mutations cause autosomal recessive Parkinson's disease (PD); however, the role of monoallelic PRKN mutations as a risk factor for PD remains unclear. We investigated the role of single heterozygous PRKN mutations in three large independent case-control cohorts totalling 10 858 PD cases and 8328 controls. Overall, after exclusion of biallelic carriers, single PRKN mutations were more common in PD than controls conferring a >1.5-fold increase in the risk of PD [ P -value ( P ) = 0.035], with meta-analysis (19 574 PD cases and 468 488 controls) confirming increased risk [Odds ratio (OR) = 1.65, P  = 3.69E-07]. Carriers were shown to have significantly younger ages at the onset compared with non-carriers (NeuroX: 56.4 vs. 61.4 years; exome: 38.5 vs. 43.1 years). Stratifying by mutation type, we provide preliminary evidence for a more pathogenic risk profile for single PRKN copy number variant (CNV) carriers compared with single nucleotide variant carriers. Studies that did not assess biallelic PRKN mutations or consist of predominantly early-onset cases may be biasing these estimates, and removal of these resulted in a loss of association (OR = 1.23, P  = 0.614; n  = 4). Importantly, when we looked for additional CNVs in 30% of PD cases with apparent monoallellic PRKN mutations, we found that 44% had biallelic mutations, suggesting that previous estimates may be influenced by cryptic biallelic mutation status. While this study supports the association of single PRKN mutations with PD, it highlights confounding effects; therefore, caution is needed when interpreting current risk estimates. Together, we demonstrate that comprehensive assessment of biallelic mutation status is essential when elucidating PD risk associated with monoallelic PRKN mutations.